The COVID-19 pandemic art of Anna Szpakowska-Kujawska: from pastels to spatial compositions - Karolina Tomczak (Quart)
In this article, Karolina Tomczak is concerned with the latest and as yet unstudied works of renowned Wrocław artist Anna Szpakowska-Kujawska (born in 1931) created during the pandemic. These works include a series of pastels Kwadraty zaokienne (Squares outside the Window, or “pandemic squares”) from 2020 and spatial objects made of polystyrene foam and cardboard executed in the years 2021–2022. Tomczak gives an analytical interpretation of the modernist element in Szpakowska-Kujawska’s artistic record of her experience of the plague as it developed from painting at the point of realistic departure to unconventional sculpture. Tomczak shows that the reworking of difficult realities in the artistic medium finally takes place in spatial objects that are transgressively modern in that they reinterpret the model of avant-garde sculpture, selected postmodern artistic solutions and Szpakowska-Kujawska’s original art. At the same time, Tomczak sees Szpakowska-Kujawska’s works as expressive objects and personal psychograms encoding reality in the subjective iconography of a special period, which stylistically determines the coexistence of individualized biomorphism and simplified figuration, abstract universalization and symbolic representation. Being an example of creative adaptation to the contemporary threat, the works are affirmations of artistic activity in everyday conditions, as well as a continuation of Szpakowska-Kujawska’s distinct version of occasionally transgressive modernism. In her methodologically concretized approach, Tomczak uses stylistic analysis and compositional interpretation, as well as contextual and partly psychoanalytic method.